Using Metaphors to Explain Molecular Testing to Cancer Patients. (April 2017) - Pinheiro, Ana P.M.; Pocock, Rachel H.; D. Dixon, Margie; Shaib, Walid L.; Ramalingam, Suresh S.; Pentz, Rebecca D.
Abstract: Background: Molecular testing to identify targetable molecular alterations is routine practice for several types of cancer. Explaining the underlying molecular concepts can be difficult, and metaphors historically have been used in medicine to provide a common language between physicians and patients. Although previous studies have highlighted the use and effectiveness of metaphors to help explain germline genetic concepts to the general public, this study is the first to describe the use of metaphors to explain molecular testing to cancer patients in the clinical setting. Methods: Oncologist‐patient conversations about molecular testing were recorded, transcribed verbatim, and coded. If a metaphor was used, patients were asked to explain it and assess its helpfulness. Results: Sixty‐six patients participated. Nine oncologists used metaphors to describe molecular testing; 25 of 66 (38%) participants heard a metaphor, 13 of 25 (52%) were questioned, 11 of 13 (85%) demonstrated understanding and reported the metaphor as being useful. Seventeen metaphors (bus driver, boss, switch, battery, circuit, broken light switch, gas pedal, key turning off an engine, key opening a lock, food for growth, satellite and antenna, interstate, alternate circuit, traffic jam, blueprint, room names, Florida citrus) were used to explain eight molecular testing terms (driver mutations, targeted therapy, hormones, receptors, resistance, exon specificity, genes, and cancer signatures). Conclusion: Because metaphors have proven to be a useful communication tool in other settings, these 17 metaphors may be useful for oncologists to adapt to their own setting to explain molecular testing terms. The Oncologist 2017;22:445–449 Implications for Practice: This article provides a snapshot of 17 metaphors that proved useful in describing 8 complicated molecular testing terms at 3 sites. As complex tumor sequencing becomes standard of care in clinics and widely used in clinical research, the use of metaphors may prove a useful communication tool, as it has in other settings. Although this study had a small sample, almost all of the patients who were exposed to metaphors in explaining molecular testing reported it as being helpful to their understanding. These 17 metaphors are examples of potentially useful communication tools that oncologists can adapt to their own practice.